Ultrastructural Investigation of the Effect of Antitumoral Agents on Adult Rat Liver - Özoğul, Candan; Tong, E.; Yamaç, Deniz; Erdoğan, Deniz (Fırat University, 2002)
Aim:The aim of the study was to investigate the influence of Adriablastina and Taxol, which are applicated together or separately for chemotherapy, in liver. Material and Method: Another group was designed to determine the effect of Cremophor – EL, which is the solvent of Taxol, to the toxicity. Sections were examined by electron microscopy. Results: In light microscopic examination mononuclear cell infiltration at portal tract was seen in taxol applied group. At the electron microscopic sections mitochondrial swelling, mitochondrial cristolysis and accumulation of collagen fiber bundles between hepatocytes were determined. In Cremophor-EL group there were no significant changes at the hepatocytes. Sinusoids were widened in Adriablastina-applied group. Portal tract was in normal structure however mononuclear cells were concerned in connective tissue. In the electron microscopic view heterochromatin was just under the cell membrane in the nucleus. The findings of both application of Adriablastina and Taxol together were approximately normal. Conclusion: According to our findings even application of antitumoral agents paclitaxel and doxorubicine separately, harmful effects on liver, especially on hepatocytes were detected. These findings suggested that the hepatotoxic agents should be used carefully to the patients who have hepatic injury.

Amaç: Çalışma kemoterapide ayrı ayrı ya da birlikte uygulanan Adriablastina ve Taxolün karaciğer üzerine etkisini incelemek amacıyla planlandı. Gereç ve Yöntem: Ayrıca Taxolün çözücüsü olan Cremophor – EL in oluşan toksisiteye etkisini belirlemek için de bir grup oluşturuldu. Alınan doku örneklerine elektron mikroskobik takip yöntemleri uygulandı. Bulgular: Çalışmada Taxol uygulanan grupta ışık mikroskobik düzeyde portal alanda mononükleer hücre infiltrasyonu gözlendi. Elektron mikroskobik düzeyde mitokondriyonlarda şişme, krista kaybı ve hepatositler arasında kollagen lif demetlerin birikmesi ilgi çekiciydi. Cremophor- EL grubunda hepatositlerde belirgin değişim izlenmedi. Adriablastina grubunda sinüzoidler genişlemişti. Portal alan normal yapıda iken ara bağ dokusunda yer yer mononükleer hücreler ilgi çekiciydi. Elektron mikroskop düzeyinde çekirdekte heterokromatinin hemen zar altında olduğu belirlendi. Adriablastina ve Taxol birlikte uygulandığında bulguların normale yakın olduğu gözlendi. Sonuç: Sonuçta antitumöral ajanlardan paklitaksel ve doksorubisinin tek başlarına uygulandıklarında da karaciğer üzerinde özellikle hepatosit düzeyinde zararlı etkilerinin olduğu gözlendi. Klinik uygulamalarda karaciğer hasarı bilinen hastalarda hepatotoksik etkili ajanların dikkatli kullanılması gereği belirlendi.
ANTİTUMÖRAL AJANLARIN ERİŞKİN SIÇAN KARACİĞERİ ÜZERİNE OLAN ETKİSİNİN İNCE YAPI DÜZEYİNDE İNCELENMESİ